2021
DOI: 10.1038/s41598-021-95767-0
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy electron beam has severe impact on seedling development compared to cold atmospheric pressure plasma

Abstract: Sprouts are germinated seeds that are often consumed due to their high nutritional content and health benefits. However, the conditions for germination strongly support the proliferation of present bacteria, including foodborne pathogens. Since sprouts are consumed raw or minimally processed, they are frequently linked to cases of food poisoning. Therefore, a seed decontamination method that provides efficient inactivation of microbial pathogens, while maintaining the germination capacity and quality of the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 74 publications
0
7
0
1
Order By: Relevance
“…These can be key aspects for developing and using plasma technologies in the food industry, medicine, ecology, and agriculture [ 19 ]. Research on cold plasma (CP) applications for agriculture is relatively new but an extremely rapidly developing area, as reflected by the large number of recent reviews [ 20 , 21 , 22 , 23 , 24 , 25 ]. It has been demonstrated that seed treatments with CP may have significant positive effects on germination, plant biochemical processes, photosynthesis [ 26 , 27 ], and biomass growth [ 27 , 28 ] and could increase harvest yields of numerous plant species.…”
Section: Introductionmentioning
confidence: 99%
“…These can be key aspects for developing and using plasma technologies in the food industry, medicine, ecology, and agriculture [ 19 ]. Research on cold plasma (CP) applications for agriculture is relatively new but an extremely rapidly developing area, as reflected by the large number of recent reviews [ 20 , 21 , 22 , 23 , 24 , 25 ]. It has been demonstrated that seed treatments with CP may have significant positive effects on germination, plant biochemical processes, photosynthesis [ 26 , 27 ], and biomass growth [ 27 , 28 ] and could increase harvest yields of numerous plant species.…”
Section: Introductionmentioning
confidence: 99%
“…A limitedtreatment time was chosen to avoid additional stresses such as heat stress, which induces a plethora of cellular effects [35][36][37][38]. Early germination was the macroscopic parameter used as an indicator of changes in the molecular biology, as shown in Figure 1, which is an effect observed in other studies [39].…”
Section: Discussionmentioning
confidence: 99%
“…Pekinensis ) seeds, 0–3 kGy electron treatments activated the defense mechanism to the pathogen ( Fusarium graminearum ) and reduced the infection rate, while the seed quality had not been reduced below the commercial threshold of 91.83% seed germination [ 80 ]. The stress resistance effects induced by low levels of electron beam radiation have also been reported by Waskow, and they showed that 8–60 kGy irradiation inactivated the microbial pathogens and stimulated various aspects of the plant’s development such as accelerating the germination of Lens culinaris seeds [ 47 ]. However, it must be mentioned that the specific impact on seeds also depends on the type of pathogen, the radiation source, and the seed used.…”
Section: Ionizing Physical Priming and Plant Responsesmentioning
confidence: 92%